Demographic Factors, Personality Traits, and the Performance of Cryptocurrency Traders - Prihatini, Dewi; Widakdo, Danang Sudarso Widya Prakoso Joyo (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
The study determines the relationship between demographic factors and personality traits with the performance of cryptocurrency traders. The research data is obtained from 100 cryptocurrency traders using the quota sampling method, correlational, with a quantitative approach. This study applies the Chi-square test to examine the relationship of demographic factors with performance and the Rank-Spearman test for the relationship of personality traits with performance. The results found that demographic characteristics (gender, age, length of trading) were positively associated with performance. Furthermore, personality traits (extraversion, agreeableness, conscientiousness, neuroticism, openness to experience) have negative and insignificant influences on the performance of cryptocurrency traders.